A philosophy of intellectual property - Drahos, Peter, 1955- (ANU Press, 2016)
Are intellectual property rights like other property rights? More and more of the world's knowledge and information is under the control of intellectual property owners. What are the justifications for this? What are the implications for power and for justice of allowing this property form to range across social life? Can we look to traditional property theory to supply the answers or do we need a new approach? Intellectual property rights relate to abstract objects - objects like algorithms and DNA sequences. The consequences of creating property rights in such objects are far-reaching. A Philosophy of Intellectual Property argues that lying at the heart of intellectual property are duty-bearing privileges. We should adopt an instrumentalist approach to intellectual property and reject a proprietarian approach - an approach which emphasises the connection between labour and property rights. The analysis draws on the history of intellectual property, legal materials, the work of Grotius, Pufendorf, Locke, Marx and Hegel, as well as economic, sociological and legal theory. The book is designed to be accessible to specialists in a number of fields as well as students. It will interest philosophers, political scientists, economists, and legal scholars, as well as those professionals concerned with policy issues raised by modern technologies and the information society.